Retrospective analysis of the BariClip procedure: Clinical outcomes and complication profile - Saleh Abualhaj; Anas Alyazouri; Mosleh M. Abualhaj; Lina Alshadfan; Shadi Hamouri; Obada Alaraishy; Eman Alkhawaja; Amro Mureb; Ali Aloun; Abdallah Arabyat (PLoS ONE, 2025)
Background Bariclip is an emerging non- resective bariatric device designed to restrict gastric capacity while preserving anatomical integrity. Unlike traditional sleeve gastrectomy, Bariclip implantation does not involve gastric resection, potentially minimizing surgical risk and allowing reversibility. However, data on its early efficacy and safety remain limited. Objective To evaluate short-term surgical outcomes, weight loss metrics, and comorbidity resolution among patients undergoing Bariclip implantation. Methods This retrospective observational study included 82 patients who underwent Bariclip placement at a single tertiary care center. Data were extracted from electronic medical records, operative logs, and follow-up notes. Outcomes assessed included total weight loss (TWL%) and excess weight loss (EWL%) at 2 weeks, 1, 2, 3, and 6 months postoperatively. Additional variables included operative time, hospital stay, early postoperative complications (within 30 days), reintervention rates, and changes in obesity-related comorbidities. Results The cohort had a mean age of 37.6 ± 9.9 years, with the majority being female (76.8%) and obese (mean BMI = 36.6 ± 4.7 kg/m²). Most patients (91.5%) underwent surgery for obesity management. Postoperatively, patients reported low pain scores (mean = 5.2), with no need for opioid analgesia and early mobilization in 62.2%. Complication rates were low (3.6%). Repeated measures ANOVA revealed a significant reduction in BMI over time (p < 0.001). At 6 months, mean %TWL was 20.04% ± 5.39% and mean %EWL reached 74.32% ± 40.75%. The most rapid weight loss occurred during the first three months, followed by a slower but consistent decline thereafter. Conclusion Bariclip surgery demonstrated favorable short-term safety and efficacy, with substantial weight loss and low complications rate observed within six months. These findings support Bariclip as a promising minimally invasive option for weight management in select patient populations.